Therapeutic Options for Chlamydia trachomatis Infection: Present and Future - Rafaela Rodrigues; Lara Marques; Pedro Vieira-Baptista; Carlos Sousa; Nuno Vale (MDPI AG, 2022)
Sexually transmitted infections (STIs), such as Chlamydia trachomatis (Ct) infection, have serious consequences for sexual and reproductive health worldwide. Ct is one of the most common sexually transmitted bacterial infections in the world, with approximately 129 million new cases per year. C. trachomatis is an obligate intracellular Gram-negative bacterium. The infection is usually asymptomatic, notwithstanding, it could also be associated with severe sequels and complications, such as chronic pain, infertility, and gynecologic cancers, and thus there is an urgent need to adequately treat these cases in a timely manner. Consequently, beyond its individual effects, the infection also impacts the economy of the countries where it is prevalent, generating a need to consider the hypothesis of implementing Chlamydia Screening Programs, a decision that, although it is expensive to execute, is a necessary investment that unequivocally will bring financial and social long-term advantages worldwide. To detect Ct infection, there are different methodologies available. Nucleic acid amplification tests, with their high sensitivity and specificity, are currently the first-line tests for the detection of Ct. When replaced by other detection methods, there are more false negative tests, leading to underreported cases and a subsequent underestimation of Ct infection's prevalence. Ct treatment is based on antibiotic prescription, which is highly associated with drug resistance. Therefore, currently, there have been efforts in line with the development of alternative strategies to effectively treat this infection, using a drug repurposing method, as well as a natural treatment approach. In addition, researchers have also made some progress in the Ct vaccine development over the years, despite the fact that it also necessitates more studies in order to finally establish a vaccination plan. In this review, we have focused on the therapeutic options for treating Ct infection, expert recommendations, and major difficulties, while also exploring the possible avenues through which to face this issue, with novel approaches beyond those proposed by the guidelines of Health Organizations.